Regional Disparities in Labor Market Performance in Croatia : The Role of Individual and Regional Structural Characteristics - Luo, Xubei (World Bank, Washington, DC, 2012)
The labor market performance in Croatia failed to keep pace with the moderately good overall macroeconomic development in the past few years. Youth, the less well-educated, and women face more difficulties in getting a job with a decent salary. A large part of the difference in regional labor market performance is associated with the difference in the human capital endowment. With a stagnant total employment rate, the large disparities in employment and earnings across individual groups and regions have become one of the concerns for the long-term sustainable development of the economy. Using Labor Force Survey (LFS) data from 2002-04, this paper studies the labor market performance in Croatia at the national and regional levels. The results show that both one's individual characteristics (including age, education and gender) and where he or she works plays a role in his or her employment and earnings. Regional differences in employment and earnings are reduced to a large extent when accounting for differences in individual characteristics. The simulations shed light on the effectiveness of the nationwide education policy and regional specific labor market policy, and suggest that improving human capital endowment and adjusting labor market structure are both important to rebalance regional development and enhance total welfare.